Weird/Black/Play: Turning Racial Authenticity and Professorial Performance on its Head in the Black Studies Classroom - Thompson, Wendy M. (Radical Teacher, 2022)
This essay examines the expectations placed on black faculty to act as conduits of authentic blackness and black knowing even as they are undermined and undervalued in the classroom and other institutional settings. Paying special attention to the way that racial performance, engaged learning, and the role of the black instructor converge in the black studies classroom, I offer the black/weird as a framework (departure/positioning) from which students can engage in black/weird/play, a remedy that interrupts students’ desire for a particular hegemonic racial performance from black faculty while stimulating critical collective inquiry about black history, experience, culture, and the self. As black/weird/play engages possibility, pleasure, and play while taking cues from black nerd and black popular cultures, students learn to grapple with concepts, structures, subjecthood, and everything else, from the mundane to the fantastic, as they building knowledge and connections alongside and with black faculty who must constantly maneuver the already contested grounds of teaching while black.